Preparation method of aerogel composite material doped with interface modified infrared opacifying agent
By using interface modifiers to form chemical bonding and physical entanglement between silica aerogel material and infrared sunscreen powder or fibers, the problems of uneven composite and poor interface bonding of aerogel materials are solved, and the overall performance and application potential of the material are significantly improved.
Patent Information
- Application Number
- CN202411758922.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-28
AI Technical Summary
When silica aerogel material is combined with sunscreen powder or fibers, it has problems such as uneven composite, unsolid interface bonding, powder loss, and performance attenuation, which limits the comprehensive performance of its composite material.
Through specific chemical structural design, interface modifiers are used to form strong chemical bonding and physical entanglement between silica aerogel material and infrared sunscreen powder or ceramic-based fibers to improve the interfacial performance of the composite material.
It significantly improves the interface bonding strength, stability and overall performance of aerogel materials after being combined with infrared sunscreen powder, extends its service life, and expands its application potential in the fields of thermal insulation, catalysis, adsorption and energy storage.
Smart Images

Figure CN119528542A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel composite material preparation, and in particular to a method for preparing an aerogel composite material doped with an interface-modified infrared sunscreen agent. Background Art
[0002] As a material with high porosity, low density, extremely low thermal conductivity and good adsorption performance, silica aerogel material is widely used in thermal protection of various spacecraft and aircraft. Adding sunscreen or fiber can greatly improve its thermal insulation performance at high temperature. Chinese patent CN102010179B discloses a method for preparing a silica aerogel composite thermal insulation material containing fiber. Its main feature is that a composite gel is first formed by adding fiber and infrared sunscreen to an aerogel precursor liquid, and the composite gel is treated to obtain a silica aerogel composite powder containing fiber; a small amount of binder is added and semi-dry pressing is used for pressing and forming, and composite products of various shapes are obtained by heat treatment. However, in the actual preparation process, it is found that when silica aerogel materials are composited with sunscreen powder or fiber, there are often problems such as uneven composite, weak interface bonding, powder loss, and performance attenuation, which limits the comprehensive performance of its composite material. Therefore, developing an effective interface modification method to improve the dispersibility of sunscreen powder in solution and enhance the interface compatibility and interaction between silica aerogel material and sunscreen powder or fiber has become one of the current research hotspots. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing an interface-modified infrared sunscreen aerogel composite material. The method can form strong chemical bonds and physical entanglements between the silica aerogel material matrix and the infrared sunscreen powder, and between the silica aerogel material and the ceramic-based fiber through a specific chemical structure design, thereby significantly improving the interface properties of the composite material; through the interface modification technology, the interface bonding strength, stability and overall performance of the aerogel material and the infrared sunscreen powder after composite are significantly improved, thereby expanding its application potential in the fields of thermal insulation, catalysis, adsorption and energy storage.
[0004] The purpose of the present invention is achieved through the following technical solutions: A method for preparing an aerogel composite material doped with an interface-modified infrared sunscreen agent, the steps of which include: uniformly dispersing a sunscreen agent in a silica aerogel precursor sol, stirring to form a composite sol; injecting or spraying the composite sol on a fiber substrate to form a wet gel composite material, and then subjecting the wet gel composite material to aging and supercritical drying to obtain a silica aerogel composite material; the sunscreen agent is an infrared sunscreen agent powder that has been interface-modified by an interface modifier, and the interface modifier is a compound containing at least one functional group that can form a stable chemical bond with a silanol group in an aerogel network structure and at least one functional group that can strongly interact with the infrared sunscreen agent powder. The infrared sunscreen agent powder is any one of titanium dioxide, silicon carbide, zirconium oxide, white carbon black, and iron oxide.
[0005] Furthermore, the functional group that can form a stable chemical bond with the silanol group in the aerogel network structure is any one of a silane group, an amino group and an epoxy group; the functional group that can produce a strong interaction with the infrared sunscreen powder is any one of a phosphate group, a carboxyl group and an amino group.
[0006] Furthermore, the interface modifier is composed of a coupling agent and one or more of an organic acid, an inorganic salt, and a solvent, that is, after the coupling agent is added to one or more of an organic acid, an inorganic salt, and a solvent, the interface modifier is obtained after stirring and reacting for a certain period of time. The coupling agent is a coupling agent containing any one or more functional groups of amino, epoxy, and methacryloxy; the organic acid is citric acid or malic acid; the inorganic salt is phosphate or silicate; and the solvent is any one of methanol, ethanol, and acetone.
[0007] Furthermore, the step of modifying the infrared sunscreen agent powder using the interface modifier is: adding the infrared sunscreen agent powder to the interface modifier in a uniformly dispersed manner, adsorbing the interface modifier uniformly on the surface of the infrared sunscreen agent powder by stirring or ultrasonic treatment, and then washing, filtering, and drying at normal pressure in sequence to obtain the infrared sunscreen agent powder after interface modification.
[0008] Furthermore, before using the interface modifier to modify the infrared sunscreen agent powder, the infrared sunscreen agent powder needs to be pretreated, and the pretreatment steps are: treating the infrared sunscreen agent powder by acid washing or alkali washing to remove surface impurities, then washing to neutrality, drying to remove excess moisture, and finally screening and treating with microwave radiation or air plasma.
[0009] Furthermore, the aerogel precursor sol preparation steps are: using organic modified silica sol (such as acidic, neutral and acidic organic modified silica sol, etc.) as a silicon source, adding water, solvent and catalyst (acid or alkali) to hydrolyze to form a silica colloidal particle solution, and then adding a gel accelerator (alkali or acid) to allow the colloidal particles to polymerize and grow to form a silica colloidal particle solution, which is a silica aerogel precursor solution.
[0010] Furthermore, the fiber substrate is a modified ceramic-based ultrafine fiber, and its preparation steps are: subjecting the ultrafine fiber to high temperature or acid washing or alkali washing treatment, and then surface modification with a silane coupling agent, the silane coupling agent is a conventional silane coupling agent, such as methyltrichlorosilane (MTS), aminosilane (AMO), vinyl silane (VTS), epoxy silane (EPS) and allyltrimethoxysilane (VTMS) and the like; the high temperature treatment method is baking at 100-350°C for 1h-4h h; the acid or alkali washing treatment method is to use a dilute strong acid or dilute strong alkali solution to treat for 0.5h-2h, then wash with pure water to neutrality, and dry; the surface modification of the silane coupling agent is to dilute and dissolve the silane coupling agent with an organic solvent and then spray it on the ultrafine fiber, dry it naturally or heat it at ≤60℃ for 3h-8h; the ultrafine fiber is one or two of ultrafine high silica fiber, ultrafine ceramic fiber, ultrafine alumina fiber, ultrafine mullite fiber, and ultrafine quartz fiber.
[0011] The beneficial effects of the present invention are: (1) Enhanced interfacial bonding strength: The functional groups in the interfacial modifier form strong chemical bonds with the infrared shading agent powder and the aerogel matrix, respectively, significantly improving the interfacial bonding strength. At the same time, the ultrafine fibers treated with high temperature or acid or alkali washing remove impurities and organic matter on the surface of the material, improving the wettability and surface roughness of the material. The ultrafine fibers are then modified with a silane coupling agent to further improve the interfacial bonding strength between the aerogel material and the matrix material.
[0012] (2) Improved dispersibility: The interfacial modifier acts on the surface of the infrared sunscreen agent powder particles through physical adsorption and chemical adsorption, and the amino groups in its molecules react with the hydroxyl groups on the surface of the infrared sunscreen agent powder particles to form chemical bonds, thereby changing the surface properties of the powder. In addition, other functional groups in the modifier molecules (such as methoxy groups) can be adsorbed in water or other polar solvents, further improving the dispersibility and stability of the powder, and improving its composite uniformity and bonding strength with aerogel materials and fiber materials.
[0013] (3) Improved stability: Improved thermal stability, chemical stability and mechanical strength of composite materials, extending service life.
[0014] (4) Optimizing performance: By adjusting the type and amount of the interfacial modifier, the thermal insulation, catalytic, adsorption and other properties of the composite material can be further optimized.
[0015] (5) The preparation method is simple and easy to implement, suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0017] Figure 1 The present invention is a flow chart of the preparation method.
[0018] Figure 2 It is a three-dimensional structure diagram of the interface-modified infrared sunscreen agent-doped aerogel composite material of the present invention and a partially enlarged schematic diagram thereof.
[0019] Figure 3 Comparison chart of thermal insulation performance test of silica aerogel composite materials made by doping with different interface modified infrared shading agents and keeping the temperature from room temperature to 800℃ for 20 minutes.
[0020] Figure 4 This is a physical picture of the interface-modified infrared sunscreen agent-doped aerogel composite material of the present invention, wherein Figure a is a physical picture of the aerogel-iron oxide composite material without interface modification; Figure b is a physical picture of the aerogel-iron oxide composite material after interface modification. DETAILED DESCRIPTION
[0021] The following is an explanation of the implementation of the present invention by specific specific embodiments. People familiar with the technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0022] The present embodiment provides a method for preparing a doped interface-modified titanium dioxide powder aerogel composite material, comprising the following steps: (1) Preparation of interface modifier: Select 10 g of Ƴ-aminopropyltriethoxysilane (APTES), 5 g of citric acid, and 1 g of sodium phosphate, add them to 50 ml of acetone, and stir the mixture at 60 °C for 4 h to form a uniform interface modifier.
[0023] (2) Pretreatment of titanium dioxide powder: Add 50g of titanium dioxide powder to 200ml of 0.1mol / l dilute hydrochloric acid solution, stir for 3h-5h to remove surface impurities, then wash with deionized water until the washing liquid is neutral, and remove excess water by centrifugation. The washed titanium dioxide powder is dried at 80℃-120℃ for 8h-12h, and finally sieved and treated with microwave radiation or air plasma to obtain titanium dioxide powder after impurities removal.
[0024] (3) Interface modification of titanium dioxide powder: 5 g of titanium dioxide powder after impurity removal was added to the interface modifier prepared in step 1, and reacted at 80°C-100°C for 3h-6h to uniformly coat the surface of the titanium dioxide powder with a layer of interface modifier. The product was vacuum filtered, subjected to multiple ultrasonic dispersion treatments for 0.5h-2h, and centrifuged until the washing liquid was clear. The titanium dioxide powder coated with the interface modifier was dried at 80°C-120°C for 8h-12h to obtain modified titanium dioxide powder.
[0025] (4) Modified ceramic-based ultrafine fibers: The quartz fibers are treated in a 0.5 mol / L NaOH solution at 50°C for 2-5 h, then washed with pure water until neutral, and dried; the silane coupling agent is then dissolved and diluted with an organic solvent and sprayed on the ultrafine fibers, and then dried naturally or heated at ≤60°C for 5 h.
[0026] (5) Preparation and compounding of aerogel materials: The precursor sol of aerogel materials is prepared by the sol-gel method, with alkaline organic modified silica sol as the silicon source, and an appropriate amount of catalyst (such as hydrochloric acid), solvent (such as ethanol) and water are added; the modified titanium dioxide powder is evenly dispersed in the silica aerogel precursor solution at a mass ratio of 1:5 (titanium dioxide powder: silicon source), and stirring is continued to form a uniform composite sol; the fiber substrate is laid on a mold or a belt, an appropriate amount of gel catalyst (such as an aqueous ammonia solution) is added to the composite sol, stirred evenly, and injected or sprayed on the fiber substrate to form a wet gel composite material, and then the aerogel-titanium dioxide composite material is obtained through aging, modification, and supercritical drying. Example 2
[0027] The present embodiment provides a method for preparing a doped interface-modified silicon carbide powder aerogel composite material, comprising the following steps: (1) Preparation of interface modifier: Select 5 g of Ƴ-mercaptopropyltrimethoxysilane and vinyltri(2-methoxyethoxy)silane in a mass ratio of 3:(1.5-2.5), add 5 g of sodium acrylate and acrylamide (molar ratio 1:1) and a cross-linking agent (such as 200 ml of toluene), stir well and react at 50-70°C for 1 h-3 h to obtain an interface modifier.
[0028] (2) Pretreatment of silicon carbide powder: Add 50g of silicon carbide powder to 350ml of 25%-35% (mass fraction) ammonium carbonate aqueous solution or ammonium bicarbonate aqueous solution, stir and react at 40℃-60℃ for 1h-3h to remove surface impurities, then wash with deionized water until the washing liquid is neutral, and remove excess water by centrifugation. The washed silicon carbide powder is dried at 80℃-120℃ for 8h-12h, and finally sieved and treated with microwave radiation or air plasma to obtain silicon carbide powder after impurity removal.
[0029] (3) Interface modification of silicon carbide powder: Add 5 g of the impurity-removed silicon carbide powder to the interface modifier solution prepared in step 1, and react at 80°C-100°C for 3h-6h to evenly coat the surface of the titanium dioxide powder with a layer of interface modifier. The product is vacuum filtered, subjected to multiple ultrasonic dispersion treatments for 0.5h-2h, and centrifuged until the washing liquid is clear. The titanium dioxide powder coated with the interface modifier is dried at 80°C-120°C for 8h-12h to obtain modified silicon carbide powder.
[0030] (4) Modified ceramic-based ultrafine fibers: bake the ceramic fibers at 300°C for 2.5 h, then dissolve and dilute the silane coupling agent with an organic solvent and spray it on the ultrafine fibers, then dry it naturally or heat it at ≤60°C for 6 h.
[0031] (5) Preparation and compounding of aerogel materials: The precursor sol of aerogel materials is prepared by the sol-gel method, with acidic organic modified silica sol as the silicon source, and an appropriate amount of catalyst (such as ammonia solution), solvent (such as methanol) and water are added; the modified silicon carbide powder is evenly dispersed in the silicon dioxide aerogel precursor solution at a mass ratio of 1:5-10 (silicon carbide powder: silicon source), and stirring is continued to form a uniform composite sol; the fiber substrate is laid on a mold or a belt, an appropriate amount of gel catalyst (such as nitric acid) is added to the composite sol and stirred evenly, and then injected or sprayed on the fiber substrate to form a wet gel composite material, and then the aerogel-silicon carbide composite material is obtained through aging, modification and supercritical drying. Example 3
[0032] The present embodiment provides a method for preparing a doped interface-modified iron oxide powder aerogel composite material, comprising the following steps: (1) Modification of iron oxide powder: Premix 5 ml of polyacrylic acid salt (mass fraction 43%-44%) and other modifiers with 5 g of iron oxide powder (add while stirring), then heat in a 60°C water bath and stir for 3h-6h to allow the polyacrylic acid to fully react with the pigment, and dry it at 80°C for 12h. Wash with deionized water until the washing liquid is clear, and remove excess water by centrifugation. Dry the washed iron oxide powder at 80°C-120°C for 8h-12h, and finally sieve and treat with microwave radiation or air plasma to obtain modified iron oxide powder. Modifiers such as polyacrylic acid salt act on the surface of iron oxide particles through physical adsorption and chemical adsorption, not only reacting with the hydroxyl groups on the surface of iron oxide particles, but also reacting with the Fe-O bonds in the lattice of iron oxide particles, thereby increasing the hydroxyl content on the surface of iron oxide particles, thereby enhancing the subsequent interface modification effect.
[0033] (2) Modified ceramic-based ultrafine fibers: The high-silica fiber is treated with a 0.1 mol / L dilute nitric acid solution for 3 h, then washed with pure water until neutral, and dried; the silane coupling agent is then dissolved and diluted with an organic solvent and sprayed on the ultrafine fiber, and then dried naturally or heated at ≤60°C for 5 h.
[0034] (3) Preparation and compounding of aerogel materials: The precursor sol of aerogel materials is prepared by the sol-gel method, with neutral organic modified silica sol as the silicon source, and an appropriate amount of catalyst (such as sulfuric acid), solvent (such as ethanol) and water are added; the modified iron oxide powder is evenly dispersed in the silica aerogel precursor solution at a mass ratio of 1:4-12 (iron oxide powder: silicon source), and stirring is continued to form a uniform composite sol; the fiber substrate is laid on a mold or a belt, an appropriate amount of gel catalyst (such as ammonium fluoride aqueous solution) is added to the composite sol and stirred evenly, and then injected or sprayed on the fiber substrate to form a wet gel composite material, and then the aerogel-iron oxide composite material is obtained through aging, modification and supercritical drying. Verification experiment:
[0035] 1. Material preparation: Fiber substrate: modified ultrafine ceramic-based fiber, the ultrafine ceramic fiber is subjected to high temperature or acid washing or alkali washing treatment, and then surface modified with a silane coupling agent to obtain a modified ultrafine ceramic-based fiber for standby use; the high temperature treatment method is baking at 250°C for 3 hours; the acid washing or alkali washing method is treating with a dilute strong acid or dilute strong alkali solution for 1.5 hours, then washing with pure water to neutrality, and drying; the surface modification of the silane coupling agent is to dilute and dissolve the silane coupling agent with an organic solvent and then spray it on the ultrafine fiber, and heat it at 100°C for 5 hours.
[0036] Silica aerogel precursor solution: using alkaline organic modified silica sol as the silicon source, adding an acid catalyst to hydrolyze to form a silica colloidal particle solution, and then adding alkaline solution to make the colloidal particles polymerize and grow to form a silica aerogel precursor solution for use.
[0037] Interface modifier: Select 10g of Ƴ-aminopropyltriethoxysilane (APTES), 5g of citric acid, and 1g of sodium phosphate, add them to 50ml of acetone, stir and react at 60℃ for 4h to form a uniform interface modifier for later use.
[0038] Infrared sunscreen powder: Take titanium dioxide, silicon carbide, zirconium oxide, white carbon black, and iron oxide and treat them in the following ways to obtain the corresponding infrared sunscreen powder for use. Add the infrared sunscreen powder to 350ml of 25%-35% (mass fraction) ammonium carbonate aqueous solution or ammonium bicarbonate aqueous solution, stir and react at 40℃-60℃ for 1h-3h to remove surface impurities, then wash with deionized water until the washing liquid is neutral, and remove excess water by centrifugation. Dry the washed silicon carbide powder at 80℃-120℃ for 8h-12h, and finally sieve and treat with microwave radiation or air plasma to obtain the infrared sunscreen powder after impurity removal.
[0039] Modified infrared sunscreen powder: Pre-treated titanium dioxide, silicon carbide, zirconium oxide, white carbon black and iron oxide are taken and modified using interface modifiers respectively.
[0040] 2. Aerogel material preparation: 2.1 Preparation of doped interface modified infrared sunscreen powder aerogel composite materials: The modified infrared sunscreen powder is evenly dispersed in the silica aerogel precursor solution at a mass ratio of 1:5 (infrared sunscreen powder: silicon source), and stirring is continued to form a uniform composite sol; the modified ultrafine ceramic-based fiber is laid on a mold or a belt, and an appropriate amount of gel catalyst (such as ammonia solution) is added to the composite sol and stirred evenly, and then injected or sprayed on the fiber substrate to form a wet gel composite material, and then the silica aerogel composite material is obtained through aging, modification, and supercritical drying. Repeating this step, the following aerogel-titanium dioxide composite material, aerogel-silicon carbide composite material, aerogel-zirconia composite material, aerogel-white carbon black composite material, and aerogel-iron oxide composite material are obtained in turn.
[0041] 2.2 Preparation of aerogel material without doping infrared sunscreen powder and fiber substrate: The conventional sol-gel method is combined with a supercritical drying process. An appropriate amount of gel catalyst (such as an aqueous ammonia solution) is added to the silica aerogel precursor solution and stirred evenly to form a wet gel. The wet gel is then aged, modified, and supercritically dried to obtain an aerogel material as a blank control.
[0042] 2.3 Preparation of aerogel material doped with unmodified infrared sunscreen powder and modified fiber substrate: The unmodified iron oxide powder is evenly dispersed in the silica aerogel precursor solution at a mass ratio of 1:5 (iron oxide powder: silicon source), and the mixture is stirred until a uniform composite sol is formed; the modified ultrafine ceramic-based fiber is laid on a mold or a belt, and an appropriate amount of gel catalyst (such as ammonia solution) is added to the composite sol and stirred evenly, and then injected or sprayed on the fiber substrate to form a wet gel composite material, and then the silica aerogel composite material is obtained through aging, modification, and supercritical drying. Repeat this step to obtain the following: aerogel-unmodified iron oxide composite material.
[0043] 2.4 Preparation of aerogel material doped with unmodified infrared sunscreen powder and unmodified fiber substrate: The unmodified iron oxide powder is evenly dispersed in the silica aerogel precursor solution at a mass ratio of 1:5 (iron oxide powder: silicon source), and the mixture is stirred continuously until a uniform composite sol is formed; the unmodified ultrafine ceramic-based fiber is laid on a mold or a belt, and an appropriate amount of gel catalyst (such as ammonia solution) is added to the composite sol, stirred evenly, and injected or sprayed on the fiber substrate to form a wet gel composite material, and then the silica aerogel composite material is obtained by aging, modification, and supercritical drying. Repeating this step, the following composite materials of aerogel-unmodified iron oxide and unmodified substrate are obtained in turn.
[0044] 3. Performance testing Aerogel material, aerogel-titanium dioxide composite material, aerogel-silicon carbide composite material, aerogel-zirconium oxide composite material, aerogel-white carbon black composite material, aerogel-iron oxide composite material, aerogel-unmodified iron oxide composite material, aerogel-unmodified iron oxide and unmodified substrate composite material (marked with serial numbers AH in sequence).
[0045] 3.1 Comparison of thermal conductivity The thermal conductivity (unit: W / (m∙k)) of materials AH was tested at room temperature and 800°C respectively. The test results are shown in Table 1.
[0046] Table 1 Thermal conductivity test of materials at room temperature and 800℃
[0047] From Table 1, we can see that: (1) Under normal temperature conditions, the thermal conductivity of the silica aerogel composite materials obtained by doping modified or unmodified infrared sunscreen powder with a fiber substrate (materials B to H) is not much different from that of the aerogel material obtained by not doping infrared sunscreen powder with a fiber substrate (aerogel material A).
[0048] (2) At 800°C, the thermal conductivity of the silica aerogel composite materials (materials B to F) obtained by doping with modified infrared sunscreen powder and modified fiber substrate was significantly reduced compared with that of aerogel material A. This indicates that after doping with modified infrared sunscreen powder and modified fiber substrate, the thermal conductivity of the silica aerogel composite materials (materials B to F) can be significantly reduced at high temperatures, thereby improving their thermal insulation properties.
[0049] (3) At 800°C, the thermal conductivity of the silica aerogel composite material (materials G and H) obtained by doping with unmodified infrared sunscreen powder or unmodified fiber substrate is between that of aerogel material A and that of the silica aerogel composite material (material F) obtained by doping with modified infrared sunscreen powder and modified fiber substrate. The thermal conductivity of materials G and H is not much different from that of material A, and the thermal conductivity of materials G and H is significantly higher than that of material F. This indicates that doping with modified infrared sunscreen powder and modified fiber substrate can significantly reduce the thermal conductivity of the prepared silica aerogel composite material (material F) at high temperature and improve its thermal insulation performance. In addition, both the infrared sunscreen powder and the fiber substrate must be modified when added, otherwise the thermal conductivity will increase and the thermal insulation performance will deteriorate.
[0050] (4) At 800°C, the thermal conductivity of the silica aerogel composite material (material G) obtained by doping unmodified infrared sunscreen powder with modified fiber substrate is significantly lower than that of the silica aerogel composite material (material H) obtained by doping unmodified infrared sunscreen powder with unmodified fiber substrate. This indicates that modifying the fiber substrate before doping the fiber substrate can reduce the thermal conductivity of the silica aerogel composite material at high temperature and improve the thermal insulation performance of the silica aerogel composite material.
[0051] 3.2 Comparison of thermal insulation performance The thermal insulation performance of materials AH was tested respectively. During the test, the materials were placed at the detection port of the heating chamber, with one side of the material (hot side) sealed at the detection port of the heating chamber and facing the interior of the heating chamber, and the other side of the material (cold side) facing away from the interior of the heating chamber. Then the room temperature was raised to 800℃ and kept constant for 20 minutes. The temperature change of the side facing away from the interior of the heating chamber (cold side) was measured (thermal insulation performance test). The test results are shown in the figure. Figure 3 shown.
[0052] Depend on Figure 3 It can be seen that: (1) During the process of being kept at a constant temperature of 800°C for 20 minutes, as time increases, the temperature and temperature rise of the cold surface of the silica aerogel composite materials (materials B to H) obtained by doping with infrared sunscreen powder and fiber matrix are significantly lower than the temperature and temperature rise of the cold surface of material A. This indicates that doping with infrared sunscreen powder and fiber matrix during the preparation of silica aerogel composite materials can significantly improve the thermal insulation performance of silica aerogel composite materials at high temperatures.
[0053] (2) During the process of being kept at a constant temperature of 800°C for 20 minutes, as time increases, the temperature and temperature rise of the cold surface of the silica aerogel composite material (materials B to F) obtained by doping with modified infrared sunscreen powder and modified fiber substrate are significantly lower than the temperature and temperature rise of the cold surface of the silica aerogel composite material (material G) obtained by doping with unmodified infrared sunscreen powder and modified fiber substrate. This indicates that the interface modification of the infrared sunscreen powder before doping with the infrared sunscreen powder can significantly improve the thermal insulation performance of the silica aerogel composite material at high temperatures.
[0054] (3) During the 20-min constant temperature treatment at 800°C, as time went on, the cold surface temperature and temperature rise of the silica aerogel composite material (material G) obtained by doping unmodified infrared sunscreen powder with modified fiber substrate were significantly lower than those of the silica aerogel composite material (material F) obtained by doping unmodified infrared sunscreen powder with unmodified fiber substrate. This indicates that modifying the fiber substrate before doping the fiber substrate can significantly improve the thermal insulation performance of the silica aerogel composite material at high temperatures.
[0055] Depend on Figure 4 It can be seen that: The silica aerogel composite material obtained by doping modified iron oxide powder and modified fiber substrate is first interface-modified between the infrared sunscreen agent powder and the fiber substrate before being doped with the infrared sunscreen agent powder, which can effectively improve the dispersion uniformity of the infrared sunscreen agent powder in the silica aerogel composite material.
[0056] Other aspects of the present invention that are not described in detail are all conventional techniques known to those skilled in the art.
[0057] It should be noted that the terms "comprises", "includes" or any other variations are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0058] The protection scope of the present invention is not limited to the technical solutions disclosed in the specific implementation methods. Any modifications, equivalent replacements, improvements, etc. made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.
Claims
1. A method for preparing an aerogel composite material doped with an interface-modified infrared sunscreen agent, comprising the steps of: uniformly dispersing the sunscreen agent in a silica aerogel precursor sol, and stirring to form a composite sol; injecting or spraying the composite sol on a fiber substrate to form a wet gel composite material, and then subjecting the wet gel composite material to aging and supercritical drying to obtain a silica aerogel composite material; characterized in that: The sunscreen agent is an infrared sunscreen agent powder that has been interface-modified by an interface modifier. The interface modifier is a compound containing at least one functional group that can form a stable chemical bond with the silanol group in the aerogel network structure and at least one functional group that can strongly interact with the infrared sunscreen agent powder.
2. The method for preparing the interface-modified infrared sunscreen agent-doped aerogel composite material according to claim 1, characterized in that: The functional group capable of forming a stable chemical bond with the silanol group in the aerogel network structure is any one of a silane group, an amino group and an epoxy group; the functional group capable of generating a strong interaction with the infrared sunscreen powder is any one of a phosphate group, a carboxyl group and an amino group.
3. The method for preparing the interface-modified infrared sunscreen agent-doped aerogel composite material according to claim 2, characterized in that: The interface modifier is composed of a coupling agent and one or more of an organic acid, an inorganic salt and a solvent.
4. The method for preparing the interface-modified infrared sunscreen agent-doped aerogel composite material according to claim 3, characterized in that: The coupling agent is a coupling agent containing any one or several functional groups of amino, epoxy and methacryloxy groups; the organic acid is citric acid or malic acid; the inorganic salt is phosphate or silicate; and the solvent is any one of methanol, ethanol and acetone.
5. The method for preparing the interfacially modified infrared sunscreen agent-doped aerogel composite material according to claim 4, characterized in that: The steps of modifying the infrared sunscreen agent powder using the interface modifier are as follows: uniformly dispersing the infrared sunscreen agent powder into the interface modifier, uniformly adsorbing the interface modifier on the surface of the infrared sunscreen agent powder by stirring or ultrasonic treatment, and then washing, filtering, and drying at normal pressure in sequence to obtain the infrared sunscreen agent powder after interface modification.
6. The method for preparing the interface-modified infrared sunscreen agent-doped aerogel composite material according to claim 5, characterized in that: Before using the interface modifier to modify the infrared sunscreen agent powder, the infrared sunscreen agent powder needs to be pretreated. The pretreatment steps are: treating the infrared sunscreen agent powder by acid washing or alkali washing to remove surface impurities, then washing to neutrality, drying to remove excess moisture, and finally screening and treating with microwave radiation or air plasma.
7. The method for preparing the interfacially modified infrared sunscreen agent-doped aerogel composite material according to any one of claims 1 to 6, characterized in that: The preparation steps of the silica aerogel precursor sol are as follows: using organic modified silica sol as a silicon source, adding solvent, water, acid or base catalyst for hydrolysis to form a silica colloidal particle solution, and then adding a gel accelerator to make the colloidal particles polymerize and grow to form a silica colloidal particle solution, which is the silica aerogel precursor solution.
8. The method for preparing the interface-modified infrared sunscreen-doped aerogel composite material according to claim 7, characterized in that: The organic modified silica sol is any one of acidic, neutral and alkaline organic modified silica sol.
9. The method for preparing the aerogel composite material doped with an interface-modified infrared sunscreen agent according to any one of claims 1 to 6, characterized in that: The infrared sunscreen powder is any one of titanium dioxide, silicon carbide, zirconium oxide, white carbon black and iron oxide.
10. The method for preparing the aerogel composite material doped with an interface-modified infrared sunscreen agent according to any one of claims 1 to 6, characterized in that: The fiber substrate is a modified ceramic-based ultrafine fiber, and its preparation steps are: subjecting the ultrafine fiber to high temperature or acid washing or alkali washing treatment, and then surface modification with a silane coupling agent; the high temperature treatment method is baking at 100-350°C for 1h-4h; the acid washing or alkali washing treatment method is treating with a dilute strong acid or dilute strong alkali solution for 0.5h-2h, and then washing with pure water to neutrality, and drying; the surface modification of the silane coupling agent is diluting and dissolving the silane coupling agent with an organic solvent and then spraying it on the ultrafine fiber, drying it naturally or heating it at ≤60°C for 3h-8h; the ultrafine fiber is one or two of ultrafine high-silica fiber, ultrafine ceramic fiber, ultrafine alumina fiber, ultrafine mullite fiber, and ultrafine quartz fiber.
Citation Information
Patent Citations
Method for preparing fiber-containing silicon dioxide aerogel composite thermal insulation material
CN102010179B
Cited By
An infrared radiation resistant fiber-reinforced aerogel material and method of making the same
CN122725785A